Apoio matricial em saúde mental na atenção primária - da concepção aos desafios: revisão integrativa da literatura - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
INTRODUCTION: Matrixing or matrix support is a way of producing health in which two or more teams, in a process of shared construction, create a proposal for pedagogical-therapeutic intervention in the field of mental health. OBJECTIVE: To synthesize results obtained in research on the practice of matriculation in mental health in primary care, based on the guidelines of the Practical Guide to Matrixing in Mental Health of the Ministry of Health. METHOD: Integrative literature review, considering publications from the period 2011- 2020, elaborated in six stages: identification of the theme and formulation of the research question to prepare the review; sampling and establishment of inclusion and exclusion criteria for the researched articles; extraction of data from primary studies; evaluation of the articles included in the review; analysis and synthesis of the results of the review and; presentation of the results of the integrative review. LILACS, BDENF, Index Psi IBECS databases were used as information sources. The controlled descriptors "health personnel", "mental health", "primary health care" and the keyword "matrix support" were used in Portuguese, English and Spanish. RESULTS: Five articles were selected that met the inclusion criteria, classified by virtue of scientific evidence and arranged in a summary table for descriptive analysis. Of these, in the databases: 50% LILACS, 25% BDENF, 12.5% INDEX PSI and 12.5% MEDLINE. Of those eligible, 100% are from Brazilian publications. It is noteworthy that 02 (40%) journals were in the area of Collective Health. As for the years of publication, the greatest occurrences were between the years 2014 and 2020. Regarding the training of the main authors, 60% nurses, 20% doctors and 20% psychologists. The highest concentration of publication of published articles was in Brazil (100%) and the southern region (60%). As for the study design, there was a predominance of qualitative studies (100%). The population investigated in the manuscripts was mostly health professionals who worked in primary health care, notably in the family health strategy. Based on the AHRQ, 100% of the articles were classified as level of evidence VI (evidence based on descriptive and qualitative studies). Regarding the thematic categories formulated based on the Ministry of Health's practical mental health guide, 60% evidenced the importance of matrix support in mental health, 80% contemplate therapeutic instruments and interventions, 100% experience the most common mental health situations and 100% highlighted the difficulties in understanding what matrix support is and the excessive demands for the FHS as the main challenges for the practice of matrix support in primary care. CONCLUSION: The conclusions of all articles, point out that the conception of primary health care professionals about matriculation in mental health is still not clear and there are many uncertainties and mistaken expectations on the part of these professionals. The scarce definitions have identified the relevance of matrix support as a strategy of decentralization and de-responsibility of specialized services in mental health care.
Keywords: Serviços de saúde mental - Avaliação; CIENCIAS DA SAUDE; Pessoal da saúde; Saúde mental; Atenção primária a saúde